2022
DOI: 10.1186/s12890-022-02114-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between leukocyte telomere length and chronic obstructive pulmonary disease is partially mediated by inflammation: a meta-analysis and population-based mediation study

Abstract: Background Chronic obstructive pulmonary disease (COPD) is one of the major health issues worldwide. Pathophysiological changes in COPD are mainly reflected in the deterioration of lung function with aging. Methods Considering that telomere length is a hallmark of biological aging, we first performed a meta-analysis to summarize the current knowledge about the relationship between telomere length and COPD and then employed individual-level data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Consistent with our ndings, previous research has indicated a negative correlation between leukocyte telomere length (LTL) and leukocyte counts [26]. A separate investigation suggested that in ammatory markers, including levels of C-reactive protein, leukocyte count, and neutrophil count in the bloodstream, may play a role in the pathogenesis of chronic obstructive pulmonary disease (COPD) through associations with shortened telomeres [27]. Additionally, the current research has unveiled a genetic association between leukocyte count and pelvic organ prolapse (POP), consistent with the ndings of the initial exome chip analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our ndings, previous research has indicated a negative correlation between leukocyte telomere length (LTL) and leukocyte counts [26]. A separate investigation suggested that in ammatory markers, including levels of C-reactive protein, leukocyte count, and neutrophil count in the bloodstream, may play a role in the pathogenesis of chronic obstructive pulmonary disease (COPD) through associations with shortened telomeres [27]. Additionally, the current research has unveiled a genetic association between leukocyte count and pelvic organ prolapse (POP), consistent with the ndings of the initial exome chip analysis.…”
Section: Discussionsupporting
confidence: 91%
“…This notion is further supported by a meta-analysis of nine European studies conducted by Albrecht et al [ 76 ]. Interestingly, none of the studies analyzed by Albrecht et al was included in the present SR. Another meta-analysis, conducted by Wang et al in 2022, reaffirmed that telomere shortening may indeed be a biomarker of accelerated aging in COPD [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…This variant was associated with reduced FEV 1 [ 34 ]. In addition, studies continue to show the importance of telomere shortening in the development of COPD [ 35 ]. This led to an insightful conversation among the panellists about the potential to screen for individuals at risk of COPD using telomere length and polygenic risk scores.…”
Section: Scientific Year In Reviewmentioning
confidence: 99%